JSW Steel's Ispat acquisition (A) : the opportunity - Sharma, Sunil, (SAGE Knowledge. Cases., 2016)
Indian steel company JSW Steel is considering the acquisition of rival company, Ispat. JSW has long considered Ispat for acquisition, and it would help them meet their high growth goals. However, Ispat carries with it a good deal of risk as a company. JSW must consider the state of the market, Ispat's advantages and disadvantages, as well as its own stability and capabilities before making a decision to acquire. To make matters more complicated, many other companies are considering an acquisition of Ispat, and JSW must make a decision now.